A Novelty of Impact of Social Media from the Legal Perspective - Andriati, Syarifah Lisa (Jurnal Jurisprudence, 2018)
Along with the development of science and technology, human life is growing dynamically, especially in the field of information and communication. The Cyber Era has produced internet technology and brought a new phenomenon in the area of mass media which also creates new media that is commonly called social media or social networking. Social media is like a two-edged knife. If used wisely, selectively and responsibly, various social networking sites can be useful, but if used irresponsibly, social media can have unfavorable consequences, and even cause legal problems.